2021
DOI: 10.2147/jir.s315957
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Models for HCC Prognosis, Recurrence Risk, and Immune Infiltration Based on Two Exosomal Genes: MYL6B and THOC2

Abstract: Introduction: Hepatocellular carcinoma (HCC) is a heterogeneous molecular disease with complex molecular pathogenesis that influences the efficacy of therapies. Exosomes play a crucial role in tumorigenesis and poor disease outcomes in HCC. Objective: The aim of this study was to identify the optimal gene set derived from exosomes in HCC with substantial predictive value to construct models for determining prognosis, recurrence risk and diagnosis and to identify candidates suitable for immunotherapy and chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Low-expression THOC2 patients had higher sensitivity to chemotherapy. 17 In addition, recent experiments had confirmed that THOC4 is the drug target of neuroblastoma. 43 Therefore, the research of THO complex members in the direction of targeted treatment of HCC has great potential and further research is very necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low-expression THOC2 patients had higher sensitivity to chemotherapy. 17 In addition, recent experiments had confirmed that THOC4 is the drug target of neuroblastoma. 43 Therefore, the research of THO complex members in the direction of targeted treatment of HCC has great potential and further research is very necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of the immune checkpoints including PD1 and CTLA4 were positively correlated with THOC2 expression in HCC, which had a significant function in regulating the activation of T cells. 17 THOC4, one of the components of T cell enhanceosome, was involved in T cell maturation and provided the molecular basis for the expression of MHC class I genes. 50 As a cytoplasmic substrate for Fms tyrosine kinase activated by macrophage colony-stimulating factor, THOC5 was directly involved in the differentiation of macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al 85 believed that exosomal miR-125b may be a reliable biomarker for the diagnosis and evaluation of extrahepatic metastasis of HCC. Zhu et al 91 established a prognosis and recurrence risk prediction model, which presented a significant predictive performance, based on two exosomal genes (MYL6B and THOC2). These findings provide a foundation for improving the early detection of HCC via identifying molecular markers.…”
Section: Potential Clinical Applications Of Exosomes In Hcc Drug Resi...mentioning
confidence: 99%
“…6,7 Immunotherapy that activates tumor-specific immune response has brought new hope for the treatment of HCC. 8 The liver is the largest immune organ in the body, rich in a variety of immune cells. 9 HCC tumor immune microenvironment is extremely complex, which is composed of cross-linking between tumor components (such as cancer cells, stromal cells and immune cells).…”
Section: Introductionmentioning
confidence: 99%